Mobile Application: GoFit (Fitness) - Mohd Nazri, Mohamad Zaim; Abd Aziz, Fadzillah (Journal of Computing Technologies and Creative Content, 2021)
More people are putting fitness and wellness mobile apps on their smartphones these days. Of course, nowadays, smartphone apps are widely used. A lot of things are made simpler and easier because to technology. Wearables are now having a major impact, getting more and more attention per year, mainly to apps and smartphones. People are increasingly installing fitness and wellness mobile applications on their smartphones. Recent studies agreed that around 60% of users have fitness applications on their smartphones. The major aim of this study is to create a fitness mobile app named "GoFit" that will assist users to track their wellness or fitness activities on their Android phones. It's just a matter of educating people what activities to do and how to accomplish them. There are a variety of fitness applications to choose from, each with its own set of features. The ADDIE method is used by the developers to make this project a success. The model's ADDIE steps are analysis, design, development, implementation, and evaluation. This methodology is used by developers since it is more efficient when creating a smartphone application. GoFit passed through alpha and beta testing to determine if it achieved the target and fulfilled the main objective. Overall, This application educates users on the advantages of leading a healthy lifestyle.